The Effectiveness of Using Instagram in Teaching English Pronunciation at Senior High School - Ningsih, Dwi Oktavia; Syafrizal, Syafrizal; Fargianti, Yusti (Journal of Linguistics, Literacy, and Pedagogy, 2024)
The research aimed to find out the effectiveness of using Instagram in teaching English pronunciation at SMA Negeri 4 Kota Serang. This study used a method that is quasi-experimental research. This study used a sample of tenth-grade students with a total of 60 students, 30 experimental students and 30 control class students. Both classes received a pre-test at the first researcher entering the class, and a post-test at the last researcher entering the class. The post-test results from the two classes would then be compared to find out the effectiveness of Instagram in teaching English pronunciation. Sig-2 tailed value from the experimental and control class was 0.01 and alpha (a) was 0.05, or 0.01<0.05, according to the results of the Independent Sample T-Test. It indicates that was rejected and was accepted. It is possible to conclude that Instagram was effective to improve students pronunciation.